FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA STAF SEKRETARIAT DPRD KABUPATEN BANJAR - Rizalul Gadi; Widarto Widarto (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
The purpose of this study was to determine the factors that influence the performance of the Parliement Secretariat staff, to find out the efforts that have been made to improve employee performance and to find out the obstacles found in improving employee performanceThis study uses a qualitative approach. qualitative approach is a research procedure that produces descriptive data in the form of systematic explanations of the research conducted. With a qualitative approach, the researcher conducts research on a scientific setting, meaning the researcher sees the reality in the field. In this case the researcher observed the efforts made to improve the performance of the Banjar Regency Council secretariat staff.The results showed that the factors that influenced the performance of the Banjar Regency DPRD Secretariat employees were seen from the ability consisting of education, the employees were mostly high school educated, training followed only based on duties and responsibilities, motivation of non-permanent employees based on the benefits received did not meet life necessities, supervision carried out is informal, that is by giving direction only, the condition of facilities and infrastructure is still inadequate to support work, and the physical condition of the work environment is still under repair. Efforts that have been made to improve employee performance are by participating in training, giving motivation, improving the physical condition of the work environment and procuring computers and providing an opportunity to be able to continue formal education to a higher level. Keywords : Factors, performance, parliement secretariate staff